Family Perceptions on Linear Growth in Stunted Children in Wonorejo Village, Malang District - Rahmatika, Qory Tifani; masfi, Ahmad; Gamagitta, Laras Putri (Universitas Muhammadiyah Lamongan, 2024)
Introduction Indonesia is ranked fifth among countries with the highest burden of stunting children. The role of families becomes very important in understanding and responding the nutritional status of children from the various risks of nutritional problems. This study was aimed to understand caregiver perceptions of child’s stunting.Methods: A qualitative phenomenological approach was conducted. Eleven primary caregivers of stunting children aged 24-60 months were interviewed individually. The recorded interviews were transcribed verbatim and were analyzed using thematic analysis.Results: Two major themes were identified: (i) family perceptions of children’s linear growth; and (ii) family responses in dealing with the growth statusConclusion: Families perceive stunting as a condition of failure to thrive which is characterized by short stature compared to other children of the same age. Families also reported emotional and attitude response upon learning the growth status of toddlers identified as experiencing stunting. The role of health workers is needed to provide emotional and informational supports to families in trying to fulfill nutrition in stunting childrenKeywords: Caregiver Perceptions, Linear Growth Faltering, Nutrition Fullfillment, Stunting